(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: The standard management of urethral strictures involving the anterior urethra is dorsal onlay buccal mucosa augmentation urethroplasty. This requires circumferential mobilisation of the urethra, which might cause ischemia of the urethra in addition to chordee. In this research, we managed the anterior urethral stricture, applying a dorsolateral onlay urethroplasty. Methodology: This prospective study was conducted in the Department of Urology, BIRDEM General Hospital& some private hospitals from July 2009 to June 2015, the outcomes of a total cases of 103 of one sided anterior dorsolateral onlay OMG Urethroplastywere assess and compared. Patients with anterior and recurrent urethral stricture more than 1 cm were included as study population. Urethrogram and Uroflowmetry were the mainstay of assessment. Success was defined as a maximum flow rate of>20 ml/sec., normal RGU, and/or urethroscopy. Poor outcomes were defined as the presence of obstructive urinary tract symptoms, Qmax <15 ml/sec., stricture diagnosed on retrograde urethrogram/ urethroscopy, and the need for any postoperative urethral intervention. Result: Of the 103 patients, 97 had (94.2%) successful outcome and 6 (5.8%) were failure. Four failed cases underwent optical internal urethrotomy and two patients had persistent narrowing and they were managed by BMG Urethroplasty. Follow up period was 12 months on an average. In conclusion, it can be said thatthe preservation of one sided vascular supply to the urethra and its entire muscular and neurogenic support represent significantly towards perfecting the surgical technique of urethral reconstruction using a minimally invasive approach. Conclusion: In this study, we found it to be a technically feasible, easily adoptable and finally successful procedure. Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 16-19